“They killed each other.” Rumor and distrust: two weapons in Mexico’s counterinsurgency in the 1970s - Ríos Merino, Alicia de los (Revista Tempo e Argumento, 2016)
This article addresses the insurgency and counterinsurgency Mexican phenomenon in the 1970s by studying “rumor” and “distrust” as strategies for dismantling insurgent organizations. It is methodologically grounded in triangulation of interviews with militants, hemerographic archives, and official documents of the Dirección Federal de Seguridad (DFS). Also, it generally outlines the relationship of militants who participated in the founding generation of the Liga Comunista 23 de Septiembre in northern Mexico and examines the nature of the most recurrent political violence actions in its early years. Finally, it thinks through political repression procedures in the decade under study.